KAJIAN KARAKTERISTIK LEMPUNG BOBONARO DI PROVINSI NUSA TENGGARA TIMUR - G.J. Winston Fernandez (Jurnal Jalan-Jembatan, 2007)
Bobonaro clay spreading along national road in Timor Island at East Nusa Tenggara has high plasticity and contains Montmorillonite. It is potential to swell and shrinkage on rainy and dry season. On saturated condition, shear strength included bearing capacity Bobonaro clay will decrease significantly, and will not able to support design load. The damage that happenned to asphalt pavement such as longitudinal cracks, surface deformation, and subsidance at national road between Kupang-Atambua is predicted caused by the characteristic of Bobonaro clay. Keywords : Bobonaro clay, Expansive soil, Shrinkage, Swelling..